Saints, shrines and pilgrims - Rosewell, Roger (Shire library, 2017)
In the Middle Ages, it was thought that praying at the right shrine could save you from just about anything, from madness and famine to false imprisonment and even shipwreck. Kingdoms, cities, and even individual trades had patron saints that would protect them from misfortune and bring them wealth and prosperity, and their feast days were celebrated with public holidays and pageants. With saints believed to have the ear of God, veneration of figures such as St Thomas Becket, St Cuthbert, and St Margaret brought tens of thousands of pilgrims from all walks of life to sites across the country. 'Saints, Shrines and Pilgrims' takes the reader across Britain, providing a map of the most important religious shrines that pilgrims would travel vast distances to reach, as well as descriptions and images of the shrines themselves. Featuring over 100 stunning photographs and a gazetteer of places to visit, it explains the history of pilgrimage in Britain and the importance that it played in medieval life, and describes the impact of the unbridled assault made on pilgrimage by the Reformation